The heart in antiquity : a journey through Egypt, Mesopotamia, India, China, Pre-Hispanic America and Greece - Zampieri, Fabio, 1976- (Storia della medicina (Rome, Italy) ;, 2022)
"This book represents the first systematic investigation on ancient cardiology, which includes the first civilizations of human history, such as those flourished in Mesopotamia, Pharaonic Egypt, Vedic India, and China. It includes also major pre-Hispanic civilizations at their apex, namely the Maya, Aztec and Inca, given that they shared fundamental features with the first ones. Finally, it closes with Greek medicine because it represents crucial advancements which paved the way to modern cardiology. Nothing similar have been previously attempted, and we believe that just this feature represents an important value of this work. The cardiovascular system was not well understood anywhere in antiquity. The heart and vessels were viewed as system of conduits containing all kind of physiological and pathological fluids, such as blood, sperm, sweat, urine, and feces. Arteries and veins were not distinguished from either an anatomical or a physiological point of view. Circulation was far from being understood. After millennia of ignorance, William Harvey, in 1628, demonstrated that the heart was a pump and its function was to push blood in the systemic circulation. This is rightly considered the dawn of modern cardiovascular medicine. Consequently, all ideas, theories and practices of ancient medicine were reduced to unimportant superstitions. Historians of medicine, adapting to that 'dogma', relegated pre-Harveian cardiology to roughs notes, preventing a proper historical evaluation of many centuries of cardiovascular conceptions and practices. All the ancient civilizations investigated in that book shared the conviction that the heart was the biological and spiritual center of the body, as the seat of emotions, mind, will, vital energy and the soul. That the heart maintained a special role both in religion and in medicine across millennia, surviving from cultural and scientific revolutions, deserves to be investigated and, possibly, explained. During the last decades, new advancements in cardiovascular and neurological physiology and pathology, shed new light on ancient ideas. Researchers are focusing on the so-called brain-heart axis, which demonstrate how these organs are strictly interconnected. Moreover, the role of the heart in emotions is becoming even more important. Indeed, ancient conceptions about the heart are founding a new validation in the physiological and neurological ground. Therefore, a first attempt of rediscovering the earliest theories and practices of cardiovascular medicine couldn't wait any longer. Finally, the celebration for the eight centuries of the University of Padua (1222-2022), represented the best occasion to undertake such an ambitious project. We hope to have been able to reach the goal, at least in the form of an original work which might inspire further researches and discoveries."--Page 4 of cover.